Strategy Development of Halal Industry for an Improved Competitiveness of MSMEs: An Analytic Network Process Approach - Lina Marlina; Joni Joni; Yadi Janwari (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
So far, there have been limited studies examining the strategies to develop the halal industry and improve the competitiveness of MSMEs in East Priangan, a high-potential area in West Java, Indonesia. Thus, this research focuses on the development of the halal industry to enhance the competitiveness of MSMEs in the area. The study utilized the analytic network process (ANP) approach and a structured questionnaire to identify suitable strategies. Seven key respondents, including academics and practitioners, were selected based on their expertise. The analysis yielded three key criteria for strategies: (1) education for MSMEs, (2) integrated financing, and (3) an MSME database. The top priority strategies include strengthening human resource capacity, halal literacy, and financing support. The research provides recommendations for MSMEs and regulatory agencies to improve competitiveness, serving as a reference for future relevant studies.